BEYOND PROFIT: INTEGRASI GOOD CORPORATE GOVERNANCE DAN KEPUTUSAN INVESTASI STRATEGIS UNTUK MENANGKAL FINANCIAL DISTRESS - Devi, Salma Pretyan; Sari, Shinta Permata (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Financial distress is a condition of declining corporate financial performance or the final stage before a company goes bankrupt, better known as liquidation. This study aims to examine the effect of the integration of good corporate governance and strategic investment decisions on financial distress in basic materials sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Good corporate governance is proxied by the board of directors, managerial ownership, and audit committee, while strategic investment decisions are measured by total assets growth and capital expenditure. Financial distress is measured using the Altman Z-Score model and classified into a dummy variable. This research employs a quantitative approach with purposive sampling, resulting in 69 companies and 207 observations. Data are analyzed using binary logistic regression. The results indicate that managerial ownership, total assets growth, and capital expenditure have effect on financial distress, while the board of directors and audit committee show no effect. These findings highlight that effective governance integration and well-planned strategic investment decisions plays a crucial role in strengthening corporate financial resilience and mitigating the risk of financial distress.